Will there be new trends in the public’s attention to express services in the post-COVID-19 era? - Xin Chen; Jie Gao; Qin Qin; Chuanlei Wang (PLoS ONE, 2026)
To explore the evolution trends and sentiment characteristics of public’s attention toward express services following the comprehensive adjustment of COVID-19 prevention policies in China, and to provide empirical evidence for service quality improvement and regulatory policy optimization, this paper uses Weibo data from December 10, 2022, to January 10, 2023 as research samples. This paper employs the Entropy Weight Method (EWM) to quantify post popularity and identify high-attention content, applies the Dynamic Topic Modeling (DTM) to uncover temporal patterns of public attention themes, and constructs a CNN-LSTM model for sentiment analysis to reveal cognitive differences between official certification bloggers and personal certification bloggers. The findings include: (1) Public sentiment toward express services was predominantly negative, and sentiment fluctuations were highly correlated with logistics pressure events such as the “Double 12” shopping festival, pandemic infection peaks, and the New Year’s Day holiday; (2) Six core topics were identified, with “goods safety” and “after-sales service” representing persistent traditional attention, while “courier rights” and “governments’ requirements for enterprises” emerged as two new trends in the post-pandemic era; (3) Official certification bloggers adopted a macro perspective focusing on enterprise service quality and logistics economy, whereas personal certification bloggers emphasized micro-level experiences regarding last-mile delivery conflicts and labor rights, with both groups converging on the issue of “courier rights.” In the post-COVID-19 era, public’s attention to express services has extended beyond efficiency and quality demands to encompass deeper dimensions such as labor rights protection and corporate social responsibility. Express enterprises should strengthen courier team building and optimize service processes, while governments need to improve industry standard-setting and regulatory incentive mechanisms to promote sustainable industry development.